Rekonstruksi Regulasi Perlindungan Data Pribadi Berbasis Blockchain Guna Mendukung Transformasi Digital Berdasarkan Teori Perlindungan Hukum - Reisya Thalita Nurmeyanka; Kumala Dian Pangesti (UIN Syarif Hidayatullah Jakarta, 2025)
Digital transformation advancements support the development of digitalization in Indonesia to realize Sustainable Development Goals (SDGs). However, this is not spread from rampant cases of data leakage due to the absence of institutions of personal data protection and the regulation certainty to regulates the mechanism protection of public data. Overlapping regulations between the institutions create legal loopholes, so that handling by the government cannot be applied optimally. Besides that, the minimum od the technology mechanism in management of personal data protection also contributes to the problem. The objective of this study is to propose a solution highlighting the necessity for clearer regulations in the implementation of blockchain-based data protection mechanisms in Indonesia, through a comparative analysis with the mechanisms applied in the European Union. The research method used id normative juridical method conceptual approach, comparative approach, and statutory approach. The result of this research concluded that the absence of the personal data protection institutions and the overlapping regulation resulting in the prevalence of the data leakage cases in Indonesia. Therefore, required the reconstruction of the personal data protection regulation and the urgency establishment of personal data protections institution with blockchain-based to provide legal protection for every society.